2010
DOI: 10.1177/0165025409360290
|View full text |Cite
|
Sign up to set email alerts
|

All they need is love? Placing romantic stress in the context of other stressors: A 17-nation study

Abstract: The present study focuses on romantic stress and coping styles in the context of identity and future-related stressors in 8,654 adolescents with a mean age of M = 15.3; SD = 1.84. The adolescents from 17 countries were grouped into seven regions, i.e., Mid-Europe, Northern Europe, Eastern Europe, Southern Europe, South Africa, South America, and the Middle East. Future-related stressors were perceived as being more stressful than romantic stressors by all adolescents, irrespective of the region in which they l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…However, they also named more negative characteristics; furthermore, conflicts were frequent, and jealousy was quite high, thus reflecting the challenging nature of these early romantic encounters (Collins et al, 2009). In accordance with other studies (Joyner & Udry, 2000;Puente & Cohen, 2003;Seiffge-Krenke et al, 2010), females in our study reported greater jealousy than males did, and they were also more active in solving problems in the romantic domain. Males felt, in general, less comfortable in being close and dependent on their female partners.…”
Section: Correlates Of Relationship Functioning In Adolescent Couplessupporting
confidence: 93%
See 1 more Smart Citation
“…However, they also named more negative characteristics; furthermore, conflicts were frequent, and jealousy was quite high, thus reflecting the challenging nature of these early romantic encounters (Collins et al, 2009). In accordance with other studies (Joyner & Udry, 2000;Puente & Cohen, 2003;Seiffge-Krenke et al, 2010), females in our study reported greater jealousy than males did, and they were also more active in solving problems in the romantic domain. Males felt, in general, less comfortable in being close and dependent on their female partners.…”
Section: Correlates Of Relationship Functioning In Adolescent Couplessupporting
confidence: 93%
“…The participants were requested to identify all coping strategies (0 = coping strategy not used, 1 = coping strategy used) they used when stress in the romantic domain occurred. Factor analysis on diverse samples revealed three factors (Seiffge-Krenke et al, 2010) representing the following coping styles: (1) active coping, including seven strategies such as seeking advice or emotional assistance from friends or negotiating with the romantic partner, (2) internal coping, including seven strategies focusing on cognitive efforts such as recognizing one's own limitations and being willing to accept compromises, and (3) withdrawal, including six strategies reflecting efforts to withdraw from the stressor or avoid the problem as well as behaviors intended to release emotional tension. Scores for the active and internal coping strategies ranged from 0 to 7 and the scores for the withdrawal strategies ranged from 0 to 6, with higher scores on each scale indicating a greater number of strategies employed to cope with romantic stress.…”
Section: Instrumentsmentioning
confidence: 99%
“…It includes behavioral, emotional, and cognitive attempts to manage the demands imposed by such stressors (Lazarus 1998). Analyses of coping strategies on adolescent samples have revealed several higher-order coping categories, such as seeking support (Seiffge-Krenke 1995), information seeking (Skinner and Zimmer-Gembeck 2007), negotiating (Seiffge-Krenke et al 2010;Skinner et al 2003), emotion regulation and escape (Skinner and Zimmer-Gembeck 2007), or withdrawal (Compas et al 2001;Seiffge-Krenke and Klessinger 2000).…”
Section: Minor Stressors and Coping Behavior In Adolescencementioning
confidence: 99%
“…Both instruments have been widely used in diverse crosscultural samples such as Finland (Seiffge-Krenke 1992), Israel (Seiffge-Krenke and Shulman 1990), Switzerland (Steinhausen and Winkler-Metzge 2001), Hong Kong (Tam and Lam 2005), Portugal (Cleto and Costa 1996) as well as in a cross-cultural study including many countries (Seiffge-Krenke et al 2010). In order to ensure cross-cultural validity and equivalence in the cross-cultural research reported here, collaborators, senior, and junior researchers from all 20 countries met regularly during and in between Means and standard deviations for age and the number of siblings in the participant's family, distributions of gender, and socioeconomic class are summarized international conferences.…”
Section: Procedures For Determining Cultural Validity and Equivalencementioning
confidence: 99%
“…The instruments for assessing stress (Problem Questionnaire, PQ) and coping (Coping Across Situations Questionnaire, CASQ) were originally developed on a German sample and published in English (Seiffge‐Krenke, ). Both instruments have been widely used in diverse cross‐cultural samples (Persike & Seiffge‐Krenke, ; Seiffge‐Krenke et al., ). To ensure cross‐cultural validity and equivalence in the cross‐cultural research reported herein, collaborators from all six countries met regularly.…”
Section: Methodsmentioning
confidence: 99%